4-{2-[5-(3,5-Difluorophenyl)-2-methylthiophen-3-yl]-3,3,4,4,5,5-hexafluorocyclopent-1-en-1-yl}-1,5-dimethylpyrrole-2-carbonitrile - Liu, Gang (International Union of Crystallography, 2011)
In the title compound, C(23)H(14)F(8)N(2)S, the dihedral angles between the pyrrole and thiophene groups and the almost planar C—C=C—C unit of the cyclopentene ring (r.m.s. deviation = 0.4193 Å) are 43.6 (5) and 50.1 (2)°, respectively. The distance of 3.612 (3) Å between the potentially reactive C atoms of the two heteroaryl substituents is short enough to enable a photocyclization reaction.